The prolonged effect of film mulch and P application on lucerne forage yield in a semiarid environment - Kong, Meng; Gu, Yan-Jie; Han, Cheng-Long; Shi, Xiao-Peng; Kang, Jing; Siddique, Kadambot H. M.; Li, Feng-Min; Yuan, Zi-Qiang (Frontiers in Plant Science, 2023)
Limited water and soil phosphorus (P) availability often hampers lucerne productivity in semiarid regions. Plastic film mulch and P application typically enhance young lucerne (2-3 years) productivity by increasing soil water use and P availability. However, the prolonged impact of film mulch and P application on lucerne productivity as the stand ages remains unclear. This study conducted a 9-year field experiment on the semiarid Loess Plateau to investigate how film mulch and P application affect lucerne forage yield, soil water content, and soil fertility. The field experiment used a split-plot design with randomized blocks, in which the whole plots were with (M1) and without plastic film mulch (M0), and the split plots were four P rates (0 (P0), 9.7 (P1), 19.2 (P2), and 28.8 (P3) kg P ha −1 ). The M1 treatment produced significantly higher lucerne forage yields than the M0 treatment during the first five years, but the yield-increasing effect of film mulch gradually diminished over time, with no effect in Years 6-8, and lower yields than the M0 treatment in Year 9.Phosphorus fertilization significantly increased forage yield after Year 3 in the M0 treatment, but only in Years 3-5 in the M1 treatment. In Years 2-5, film mulch significantly increased soil organic carbon, total nitrogen (N), inorganic N, and microbial biomass carbon in P0, P1, and P2 but not in P3.However, in Years 7-9, film mulch significantly decreased soil available potassium (K), organic carbon mineralization, lucerne density, and shoot K concentration, but did not reduce soil N and P availability at any level P of application. Moreover, plastic film mulch significantly increased the soil water content at 0-300 cm deep from Year 7 onwards. In conclusion, film mulch ceased to enhance lucerne production beyond year 6, which could not be attributed to soil water content, N or P availability but was partially associated with reduced soil K availability. Consequently, future research should focus on soil K availability, and K addition should be considered after five years in lucerne pastures mulched with plastic film in semiarid areas.